Detecting Earnings Management in Transition Economies: A Longitudinal Analysis of SQB Bank, Uzbekistan - Jumaniyozov Jasur Xolmurod O’g’li; Toni Heryana; Ida Elis Mediawati; Kudratov Inomjon Nemat Ugli (Journal of Islamic Contemporary Accounting and Business, 2026)
This study examines the prevalence and determinants of earnings management (EM) practices within Sanoat Qurilish Bank (SQB), a systemic state-owned financial institution in Uzbekistan. Amidst the country's transition toward market-oriented reforms, understanding the integrity of financial reporting is crucial. Utilizing a longitudinal quantitative approach covering the period 2013–2023, this research employs a Multiple Linear Regression model to detect potential income smoothing. The study defines Net Profit as the dependent variable (proxy for reported earnings), while Return on Assets (ROA), Return on Equity (ROE), Total Assets, and Total Equity serve as independent variables representing financial performance and firm size. The empirical results demonstrate a statistically significant relationship between fluctuations in ROE and Net Profit, signaling proactive income smoothing behavior to meet performance benchmarks. Furthermore, the observed volatility in profitability ratios (ROA/ROE)—juxtaposed against the linear expansion of assets and equity—suggests the strategic use of managerial discretion. These findings corroborate agency theory and EM patterns prevalent in emerging markets where institutional governance and audit oversight are still evolving. This research contributes to the literature on financial transparency in transitional economies and provides critical insights for regulators and investors regarding the necessity of adopting IFRS-aligned oversight in Uzbekistan’s banking landscape.